Palynological characterization of the Southeast Asian woody climbers Decalobanthus Ooststr. (Convolvulaceae). Issue 5 (3rd September 2021) - Simões, Ana Rita Giraldes; Pisuttimarn, Ponprom; da Luz, Cynthia Fernandes Pinto; Furness, Carol; Pornpongrungrueng, Pimwadee; Chatrou, Lars W.
Abstract: Decalobanthus is a genus of woody climbers of Convolvulaceae, recently expanded from a monotypic genus to including 17 species, mainly distributed in Asia and the Pacific. Despite the monophyly and the strong morphological and geographical coherence of the genus, only five of its species have been sampled in a molecular phylogenetic study and their relationships remain poorly understood. As a pillar to further systematic and evolutionary studies of Decalobanthus, this study offers a full characterisation of its pollen variation. To date, only seven of the 17 species have been palynologically documented in the literature (as Merremia s.l .). We here offer new data for seven species, which adding up to the already available data, totals a characterisation of 14 out of the 17 species in the genus. The pollen of Decalobanthus is, in most cases, tricolpate, with one species presenting hexapantocolpate polymorphism, which could suggest di/polyploidy; the presence of a reticulate exine ('reticulum cristatum' type) is remarkable, in Convolvulaceae only known otherwise in some species of Cuscuta .